Generalized Hardy, Copson, Leindler and Bennett inequalities on time scales. Issue 5 (8th October 2013) - Saker, S. H.; O'Regan, D.; Agarwal, R.
<x xml:space="preserve">Abstract</x> In this paper, we prove some new dynamic inequalities on time scales using Hölder's inequality and Keller's chain rule on time scales. These inequalities, as special cases when the time scale <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg537sdg3r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />T=R</alternatives> and when <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg537sdg26" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />T=N</alternatives>, contain some generalizations of integral and discrete inequalities due to Hardy, Copson, Leindler and Bennett.